Informatics on Lithuanian schools: since sources towards the future - Ališauskas, Ričardas (Information & Media, 1994)
There are two goals of the resource on which this article is based. At first - the fixation of the school informatics history in Lithuania. The short history of the school computerization in Lithuania is presented and many another published articles are pointed out.On the second hand problems of the creating of the school informatics curriculum are investigated. The methodology of the creating of obligatorily informatics curriculum is based on the fullness of the informatics content, the necessity to control the school, the content of examination before the study in universities and the modern job, communications etc. based on computer. The hypothesis is raised there are some chances for the synthesis of both technical and social informatics in the Lithuanian school curriculum now.For this synthesis the help of specialists from universities is needed. The way for the partnership between higher and secondary schools is proposed in this article. Secondary schools are looking for special informatics curricula oriented towards studies at concrete faculties of universities and another higher schools in Lithuania. Especially the curriculum for social informatics is wanted.
Keywords: -